Предмет: Математика, автор: voldobro145

помогите ..................​

Приложения:

Ответы

Автор ответа: MatemaT123
0

Ответ:

0,4

Пошаговое объяснение:

\dfrac{\dfrac{1}{\dfrac{2}{3}-\dfrac{1}{4}}}{\dfrac{2}{\dfrac{1}{5}+\dfrac{2}{15}}}=\dfrac{\dfrac{1 \cdot 12}{(\dfrac{2}{3}-\dfrac{1}{4}) \cdot 12}}{\dfrac{2 \cdot 15}{(\dfrac{1}{5}+\dfrac{2}{15}) \cdot 15}}=\dfrac{\dfrac{12}{8-3}}{\dfrac{30}{3+2}}=\dfrac{\dfrac{12}{5}}{\dfrac{30}{5}}=\dfrac{12 \cdot 5}{5 \cdot 30}=\dfrac{12}{30}=0,4;

Похожие вопросы
Предмет: Физика, автор: Daller228